Digital-Based Learning Innovation of Health Psychology and Physical Activity to Promote Healthy Lifestyles among High School Students - Ainun Hamdani; Romadhoni (Ihsan Cahaya Pustaka, 2025)
This study develops and evaluates a digital-based learning innovation integrating health psychology and physical activity to promote healthy lifestyles among high school students. Despite the proven benefits of exercise in enhancing physical and psychological health, many adolescents neglect regular physical activity due to busy schedules and lack of motivation. The innovation combines psychological theories with interactive digital modules to increase students’ awareness and engagement in daily exercise. Using a mixed-methods approach, the module was implemented in selected schools and assessed through pre- and post-tests, questionnaires, focus groups, and interviews. Findings reveal significant improvements in students’ knowledge of health psychology, motivation for physical activity, and adoption of healthier habits. The novelty of this study lies in leveraging digital media to bridge theory and practice, providing an accessible and engaging platform for health education. This research offers valuable insights for educators and policymakers aiming to enhance adolescent well-being through innovative, technology-driven learning strategies.